Genotype–phenotype correlation in von Hippel‐Lindau disease. Issue 8 (15th March 2021) - Reich, Michael; Jaegle, Sabine; Neumann‐Haefelin, Elke; Klingler, Jan‐Helge; Evers, Charlotte; Daniel, Moritz; Bucher, Felicitas; Ludwig, Franziska; Nuessle, Simone; Kopp, Julia; Boehringer, Daniel; Reinhard, Thomas; et al.
Abstract: Background/Aims: Retinal haemangioblastomas (RH) remain a major cause of visual impairment in patients with von Hippel‐Lindau (VHL) disease. Identification of genotype–phenotype correlation is an important prerequisite for better management, treatment and prognosis. Methods: Retrospective, single‐centre cohort study of 200 VHL patients. Genetic data and date of onset of RH, central nervous system haemangioblastomas (CNSH), pheochromocytoma/paraganglioma (PPGL), clear cell renal cell carcinoma (ccRCC) and pancreatic neuroendocrine neoplasm (PNEN) were collected. The number and locations of RH were recorded. Results: The first clinical finding occurred at an age of 26 ± 14 years (y) [mean ± SD]. In 91 ± 3% (95% CI 88–94) of the patients, at least one RH occur until the age of 60y. A total of 42 different rare VHL gene variants in 166 patients were detected. A higher age‐related incidence of RH, CNSH, ccRCC and PNEN was detected in patients with a truncating variant (TV) compared to patients with a single amino‐acid substitution/deletion (AASD) (all p < 0.01), while it is reverse for PPGL (p < 0.01). Patients with a TV showed 0.10 ± 0.15 RH per y during their lifetime compared to 0.05 ± 0.07 in patients with AASD (p < 0.02). The median enucleation/phthisis‐free survival time in patients with a TV was 56y (95% CI 50–62) compared to 78y (95% CI 75–81) in patients with AASD (p < 0.02). Conclusion: Compared to patients with AASD, patients with a TV develop RH, CNSH, ccRCC and PNEN earlier. They experience a higher number of RH and bear a higher risk of enucleation/phthisis. Thus, patients with a TV might be considered for a more intensive ophthalmological monitoring.